Profil Metabolit Plasma Darah dan Aktivitas Kreatin Kinase Sapi Perah Berdasarkan Fluktuasi Mikroklimat Lingkungan Kandangnya - Mushawwir, Andi; Yulianti, An An; Suwarno, Nono; Permana, Ronnie (Jurnal Veteriner; Vol 21 No 1 (2020), 2020)
Twenty dairy cow (Fries Holland) of 3-4thlactation were used in this study to investigate metabolism rate and activities of creatin kinase (CK) in fluctuation of housing microclimate. Wet and dry ball thermometer placed in housing and around housing to record the fluctuation of temperature, relative humidity and temperature humidity index (THI). Blood sample were collected from vena jugularis weekly during five months. Whole blood centrifuged to earn plasma and all of sample was analyzing by spectophometric method, based on Biolabo Kit, France. Data was analyzed by F-test of regretion correlation, using SPSS IBM 21 Software. Based on the results in this study showed that fluctuation blood parameter following microclimate profile (P<0,05). The plasma metabolite profile and activities of CK increased in heat-stressed animal samples. As conclusion, the alteration in the profile of blood plasma metabolites were a results of the gluconeogenesis pathway activities, also increasing anaerob. In the same way, also showed in creatinine and creatine kinase levels.